1999
DOI: 10.1007/s001250051137
|View full text |Cite
|
Sign up to set email alerts
|

Islet autoantibodies in cord blood from children who developed Type I (insulin-dependent) diabetes mellitus before 15 years of age

Abstract: Type I (insulin-dependent) diabetes mellitus is a multifactorial disease that develops after exposure to unknown environmental factors in children with specific HLA susceptibility genes. At the time of clinical diagnosis, the majority of the insulin-producing cells in the pancreatic islets have been eradicated in association with autoimmune phenomena including insulitis [1 ,2, 3], lymphocyte proliferation abnormalities [4,5,6] and autoantibodies to islet cell antigens [7±9]. Studies in first-degree relatives [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 66 publications
1
79
1
Order By: Relevance
“…66 Recent studies have shown increased frequencies of autoantibodies in blood taken from infants and young children who subsequently develop diabetes, suggesting that the autoimmune process may begin very early. [31][32][33] Among relatives of type 1 diabetics, those with anti-GAD antibodies who progressed to develop diabetes ('progressors') were more likely to have anti-GAD of subclass IgG1 and/or IgG3. On the other hand, relatives with anti-GAD antibodies who did not progress to develop diabetes ('non-progressors') were more likely to have IgG2 and/or IgG4 antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 Recent studies have shown increased frequencies of autoantibodies in blood taken from infants and young children who subsequently develop diabetes, suggesting that the autoimmune process may begin very early. [31][32][33] Among relatives of type 1 diabetics, those with anti-GAD antibodies who progressed to develop diabetes ('progressors') were more likely to have anti-GAD of subclass IgG1 and/or IgG3. On the other hand, relatives with anti-GAD antibodies who did not progress to develop diabetes ('non-progressors') were more likely to have IgG2 and/or IgG4 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of autoantibodies (especially multiple antibodies at high titres) is strongly associated with risk of progressing to clinical diabetes, both in relatives of type I diabetics [30][31][32][33] and in the general population. 34 It is not clear whether these autoantibodies directly participate in ␤-cell destruction by binding with ␤-cell antigens, or whether they arise as a consequence of ␤-cell destruction following release of self-antigens from destroyed ␤-cells 35 or both.…”
Section: Introductionmentioning
confidence: 99%
“…Either way, the presence of antibodies to islet cell components (especially multiple autoantibodies at high titres) is strongly associated with risk of progressing to clinical diabetes, both in relatives of Type I diabetic patients [7] and in the general population [28]. Recent studies have shown that autoantibodies occur even in infants and young children who later develop diabetes, suggesting that the autoimmune process could begin very early in life, perhaps prenatally [8,29,30]. Because autoantibodies are biological markers for preclinical diabetes, it is important to know whether these autoantibodies show evidence for genetic determination, or whether they merely reflect the presence of non-genetic diabetes-predisposing factors (such as viruses that damage beta cells).…”
Section: Evidence For a Genetic Basis: Family And Twin Studies Of Typmentioning
confidence: 99%
“…Vitamin D has several effects on the immune system that could be of relevance in the pathogenesis of type 1 diabetes [8,9]. The process leading to the destruction of the beta cells might be initiated even before birth [10], therefore the effect of early environmental determinants in utero may be of crucial importance. Because maternal vitamin D intake and status during pregnancy affect neonatal vitamin D status [11][12][13], the former is an important area to study when searching for factors potentially involved in the development of type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%